Differential vulnerability of adult neurogenic niches to dosage of the neurodevelopmental-disorder linked gene Foxg1 - Schäffner, Iris; Wittmann, Marie-Theres; Vogel, Tanja; Lie, Dieter Chichung (Molecular Psychiatry, 2022)
The transcription factor FOXG1 serves pleiotropic functions in brain development ranging from the regulation of precursor proliferation to the control of cortical circuit formation. Loss-of-function mutations and duplications of FOXG1 are associated with neurodevelopmental disorders in humans illustrating the importance of FOXG1 dosage for brain development. Aberrant FOXG1 dosage has been found to disrupt the balanced activity of glutamatergic and GABAergic neurons, but the underlying mechanisms are not fully understood. We report that FOXG1 is expressed in the main adult neurogenic niches in mice, i.e. the hippocampal dentate gyrus and the subependymal zone/olfactory bulb system, where neurogenesis of glutamatergic and GABAergic neurons persists into adulthood. These niches displayed differential vulnerability to increased FOXG1 dosage: high FOXG1 levels severely compromised survival and glutamatergic dentate granule neuron fate acquisition in the hippocampal neurogenic niche, but left neurogenesis of GABAergic neurons in the subependymal zone/olfactory bulb system unaffected. Comparative transcriptomic analyses revealed a significantly higher expression of the apoptosis-linked nuclear receptor Nr4a1 in FOXG1-overexpressing hippocampal neural precursors. Strikingly, pharmacological interference with NR4A1 function rescued FOXG1-dependent death of hippocampal progenitors. Our results reveal differential vulnerability of neuronal subtypes to increased FOXG1 dosage and suggest that activity of a FOXG1/NR4A1 axis contributes to such subtype-specific response.
CRIS-Team WoS Importer:2022-04-08